Two‐dimensional materials: From mechanical properties to flexible mechanical sensors. Issue 6 (16th December 2019) - Jiang, Hanjun; Zheng, Lu; Liu, Zheng; Wang, Xuewen
Abstract: Two‐dimensional (2D) materials have great potential in the fields of flexible electronics and photoelectronic devices due to their unique properties derived by special structures. The study of the mechanical properties of 2D materials plays an important role in next‐generation flexible mechanical electronic device applications. Unfortunately, traditional experiment models and measurement methods are not suitable for 2D materials due to their atomically ultrathin thickness, which limits both the theoretical research and practical value of the 2D materials. In this review, we briefly summarize the characterization of mechanical properties of 2D materials by in situ probe nanoindentation experiments, and discuss the effect of thickness, grain boundary, and interlayer interactions. We introduce the strain‐induced effect on electrical properties and optical properties of 2D materials. Then, we generalize the mechanical sensors based on various 2D materials and their future potential applications in flexible and wearable electronic devices. Finally, we discuss the state of the art for the mechanical properties of 2D materials and their opportunities and challenges in both basic research and practical applications. Abstract : Two‐dimensional materials are promising for flexible electronics due to their novel mechanical, electrical, and optical properties. The mechanical induced properties of 2D materials are discussed, and their applications in flexible mechanical sensors are summarized.